The Strategic Supplier Relationships towards Effective Policy Implementation in the Ghana Armed Forces - Shaibu, Aminu Mohammed; Estiller, Renalyn (Journal of Interdisciplinary Perspectives, 2025)
The study evaluated the impact of strategic supplier relationships on the effectiveness of procurement policy implementation in the Ghana Armed Forces (GAF). The study was underpinned by the Resource-Based View of the Firm, the Strategic Sourcing and Trust theories, and the E-Procurement System Framework, which explain the connection between Strategic Supplier Relationships (SSR) and the effectiveness of policy implementation. The study employed a descriptive research design with a quantitative approach. The study relied solely on primary data, using a structured questionnaire to solicit responses from 156 respondents, including GAF personnel and other stakeholders. The research locale was Burma Camp, in Accra, Ghana's capital city. SPSS version 26 and SMART PLS version 3.8 were used for the data analysis. The analysis considered descriptive and inferential analyses (ANOVA by Factor, t-test, and Structural Equation Modelling (SEM)). The study found significant opportunities for the GAF in SSR. These include strategic alliance, transparency and accountability, long-term planning, and local sourcing. In addition, the study found that the current state of Supplier Relationship Management (SRM) implementation in GAF has a significant impact on Communication, Mutual Trust, and Supplier Performance. Furthermore, the study revealed that the Public Procurement Law significantly moderates the challenges and opportunities, as well as the SRM, in the effective implementation of the Procurement Policy in GAF. Additionally, SEM results indicate that Challenges & Opportunities and SRM have a significant influence on effective policy implementation in the GAF.